2019
DOI: 10.17222/mit.2018.122
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the properties of copper-alumina nanocomposites synthesized by mechanical alloying

Abstract: Industries use metal-matrix composites all year round, where the alloying of metals plays an important role. Many researchers have seen that an improvement in the alloying of metals possesses a great value in applications. So metal-matrix composites are being investigated for better blending of the particles for the metal constituents. This guides researchers towards the addition of many alloying elements or reinforcements to form superior-quality MMCs with smaller particle sizes. In this regard, the focus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…After that, a simulation is performed with a photovoltaic, wind turbine, integrated smart grid also as a framework that can be subjected to multiple situations, including tiny homes and offices. The simulation outcomes confirmed the efficacy and effectiveness of the implemented hybrid smart grid strategy operating in various modes [43][44][45][46][47]. A recently integrated control technique with solar cells and wind turbine resources is presented.…”
Section: Combined Microgridsmentioning
confidence: 55%
“…After that, a simulation is performed with a photovoltaic, wind turbine, integrated smart grid also as a framework that can be subjected to multiple situations, including tiny homes and offices. The simulation outcomes confirmed the efficacy and effectiveness of the implemented hybrid smart grid strategy operating in various modes [43][44][45][46][47]. A recently integrated control technique with solar cells and wind turbine resources is presented.…”
Section: Combined Microgridsmentioning
confidence: 55%
“…Several studies have been reported on the synthesis and characterization of copperalumina nanocomposites by mechanical alloying. For example, Kumar et al [37] synthesized copper-alumina nanocomposites by mechanical alloying and subsequent hotpressing. They found that the addition of alumina particles to copper matrices improved their hardness and wear resistance.…”
Section: Introductionmentioning
confidence: 99%